2020
DOI: 10.3390/pharmacy8040220
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes of Student Pharmacists Regarding Polypharmacy and Deprescribing: A Cross-Sectional Study

Abstract: Pharmacists play a key role in deprescribing medications. Incorporation of this concept into pharmacy school curricula is important in ensuring that graduates can address the complex needs of an aging population. The aims of this study were to assess if and how student pharmacists were exposed to deprescribing within their curriculum, to assess students’ perceptions regarding their attitudes, ability and confidence in deprescribing, and to assess if reported curricular exposure to this topic resulted in improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…While 97.4% of respondents believed that pharmacists played a role in deprescribing, the responses also suggested that more training is required due to a lack of confidence in deprescribing [ 11 ]. Furthermore, a cross-sectional study of student pharmacists from 132 institutions focused on deprescribing in pharmacy curricula exclusively [ 12 ]. The results showed that fewer than half of student pharmacists indicated that deprescribing instruction was part of their non-experiential education or their curriculum prepared them to deprescribe in a clinical setting, while a vast majority reported significant perceived barriers to pharmacist deprescribing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While 97.4% of respondents believed that pharmacists played a role in deprescribing, the responses also suggested that more training is required due to a lack of confidence in deprescribing [ 11 ]. Furthermore, a cross-sectional study of student pharmacists from 132 institutions focused on deprescribing in pharmacy curricula exclusively [ 12 ]. The results showed that fewer than half of student pharmacists indicated that deprescribing instruction was part of their non-experiential education or their curriculum prepared them to deprescribe in a clinical setting, while a vast majority reported significant perceived barriers to pharmacist deprescribing [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a cross-sectional study of student pharmacists from 132 institutions focused on deprescribing in pharmacy curricula exclusively [ 12 ]. The results showed that fewer than half of student pharmacists indicated that deprescribing instruction was part of their non-experiential education or their curriculum prepared them to deprescribe in a clinical setting, while a vast majority reported significant perceived barriers to pharmacist deprescribing [ 12 ]. These studies demonstrate the need for more focused, qualitative inquiry on deprescribing education in the pharmacy curriculum.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Specific to academic pharmacy, there is significant need to enhance teaching of optimal prescribing and deprescribing related content with student assessment measures in the didactic and experiential curricula. 12,15 In addition to educational content and evaluations, there are needs for further research into pharmacists' impact on deprescribing in end-of-life care settings, and to assess the need for and sustainability of palliative and hospice care pharmacists. 1 Within the American Association of Colleges of Pharmacy (AACP) Strategic Plan, academic-practice partnerships that enhance pharmacy education and promote interprofessional practice have been identified for further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…11 - 14 Specific to academic pharmacy, there is significant need to enhance teaching of optimal prescribing and deprescribing related content with student assessment measures in the didactic and experiential curricula. 12 , 15 In addition to educational content and evaluations, there are needs for further research into pharmacists’ impact on deprescribing in end-of-life care settings, and to assess the need for and sustainability of palliative and hospice care pharmacists. 1 …”
Section: Introductionmentioning
confidence: 99%
“…27,28 Many studies have assessed PPI use and deprescribing protocols but have not focused on the implementation of student-led telehealth interventions. 29,30 Telepharmacy has the potential to provide greater opportunities for patient consultation and adherence monitoring in medically underserved areas, 31 and pharmacy students, in collaboration with pharmacists, are well-positioned to aid in successful deprescribing services utilizing this model of care. This evaluation considers the integration of student pharmacists in collaboration with CPPs to deprescribe PPIs that are being used inappropriately in rural Veterans.…”
Section: Introductionmentioning
confidence: 99%